Tetrakis(triphenylarsine)copper(I) hexafluoridophosphate - Kern, Thomas (International Union of Crystallography, 2007)
In the crystal structure of the title compound, [Cu(C(18)H(15)As)(4)]PF(6), the Cu atom is coordinated by four As atoms of triphenylarsine ligands in a tetrahedral geometry. The complex cation is located on a crystallographic threefold axis. Both PF(6) (−) anions are located on special positions of site symmetry [Image: see text]. The Cu—As bond of the independent arsine ligand is shorter than the Cu—As bonds of the three symmetry-related arsine ligands.